PENINGKATAN HASIL BELAJAR IPA MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI KELAS IV SEKOLAH DASAR - RAHMAYANTI, SRI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Students are not active, creative, looked so bored, and crawded in teaching learning process, then teacher do not make alamiah of studying environment, present real think in teaching leaning is problem that cause the rresult studying of student low.the pupose of this research to describe lesson plan realization of teaching learning increase the result IPA subject of student with used contextual teaching and learning approach (CTL) in SD Negeri 14 Gurun Laweh at Ivclass. Subject of research is teacher and student at IV class that amount 26 student consist of 12 boy and 14 girl at 2011/2012 academic year. The data gotten through four steps is planning, realization, observation, and reflection. And then analysis do through qualitative and quantitative approach. The result of this research showed that activity of student increased with individual and group, find material of lesson with do experiment, showing interesting and anthusiasm in answer LKS. The result of teaching learning increase and success. Key word : the result of teaching learning, teaching learning IPA, ctl approach.